Incorporating literary fiction in teaching "Brand Management" course - focus on consumer values - Ochkovskaya, Marina; Butenina, Evgenia; Nikitin , Stanislav (Serbian Journal of Management, 2026)
The authors demonstrate how examples from literary texts deepen the understanding of consumer values in Brand Management course (according to Sheth, Newman and Gross’ classification: functional, social, emotional, epistemological, and conditional values). To understand the students’ interest in this topic and the usefulness of assignments with fragments of fiction, the authors conducted a study among MBA students who completed the Brand Management course, where these assignments were integrated. The results of the study showed that students consider these assignments interesting, useful, and broadening their erudition. Moreover, almost half of the respondents used the knowledge gained from completing the assignments with fragments of fiction in their practical activities.
Keywords: literary fiction; Brand Management; brand; consumer values